Cool nighttime temperatures induce the expression of CONSTANS and FLOWERING LOCUS T to regulate flowering in Arabidopsis - Kinmonth-Schultz, Hannah A. (New Phytol, 2016)
Day length and ambient temperature are major stimuli controlling flowering time. To understand flowering mechanisms in more natural conditions, we explored the effect of daily light and temperature changes on Arabidopsis thaliana. Seedlings were exposed to different day/night temperature and day-length treatments to assess expression changes in flowering genes. Cooler temperature treatments increased CONSTANS (CO) transcript levels at night. Nighttime CO induction was diminished in flowering bhlh (fbh)-quadruple mutants. FLOWERING LOCUS T (FT) transcript levels were reduced at dusk, but increased at the end of cooler nights. The dusk suppression, which was alleviated in short vegetative phase (svp) mutants, occurred particularly in younger seedlings, while the increase during the night continued over 2 wk. Cooler temperature treatments altered the levels of FLOWERING LOCUS M-β (FLM-β) and FLM-δ splice variants. FT levels correlated strongly with flowering time across treatments. Day/night temperature changes modulate photoperiodic flowering by changing FT accumulation patterns. Cooler nighttime temperatures enhance FBH-dependent induction of CO and consequently increase CO protein. When plants are young, cooler temperatures suppress FT at dusk through SVP function, perhaps to suppress precocious flowering. Our results suggest day length and diurnal temperature changes combine to modulate FT and flowering time.